Efficient flame retardant interplay of unsaturated polyester resin formulations based on ammonium polyphosphate. (August 2020) - Reuter, Jens; Greiner, Lara; Kukla, Philipp; Döring, Manfred
Abstract: The flame retardant effects of ammonium polyphosphate (APP) in combination with different mineral flame retardants as well as the combination of APP and phosphorus based flame retardants in unsaturated polyester resin was investigated. Flammability and thermal stability of unsaturated polyester (UP) composites were evaluated with UL-94 vertical burning, thermogravimetric analysis (TG) and cone calorimetry. The morphology of char residues was examined via scanning electron microscopy (SEM). An interaction between APP and phosphinate salts was observed. A combination of 20 wt-% APP and aluminum diethylphosphinate (AlPi) passed UL 94 V-0 classification. In contrast the combination of APP and mineral flame retardants did not show sufficient burning behavior in UL 94 vertical burning test. Furthermore, PHRR and THR was reduced by introduction of phosphinate salts or mineral flame retardants, compared with a formulation containing solely APP. SEM of the residues showed that the combination of APP and the phosphinate salts forms a though and dense residue that can protect underlying material. An incorporation of mineral fillers and APP leads to a fragile residue. Highlights: Combination of APP and phospinate salts in UP resins achieves V-0 classifications in UL 94 small burner test. In cone calorimetry tests formulations comprising APP and phosphinate salts show a reduction of PHRR andTHR compared to formulations containing solely APP. The heat release for formulations containing APP and phosphinate salts directly after ignition is reduced by about 20% compared to formulations containing APP and mineral flame retardants or APP alone. Mixtures with APP and phosphinate salts produce a dense residue, while the residues of the other mixtures are rough and brittle.